After Jesus before Christianity a historical exploration of the first two centuries of Jesus movements - Vearncombe, Erin; Scott, Bernard Brandon 1941-; Taussig, Hal E. 1947- (HarperOne, 2021)
From the creative minds of the scholarly group behind the groundbreaking Jesus Seminar comes this provocative and eye-opening look at the roots of Christianity that offers a thoughtful reconsideration of the first two centuries of the Jesus movement, transforming our understanding of the religion and its early dissemination. Christianity has endured for more than two millennia and is practiced by billions worldwide today. Yet that longevity has created difficulties for scholars tracing the religion's roots, distorting much of the historical investigation into the first two centuries of the Jesus movement. But what if Christianity died in the fourth or fifth centuries after it began? How would that change how historians see and understand its first two hundred years? Considering these questions, three Bible scholars from the Westar Institute summarize the work of the Christianity Seminar and its efforts to offer a new way of thinking about Christianity and its roots. Synthesizing the institute's most recent scholarship--bringing together the many archaeological and textual discoveries over the last twenty years -- they have found : there were multiple Jesus movements, not a singular one, before the fourth century ; there was nothing called Christianity until the third century ; there was much more flexibility and diversity within Jesus's movement before it became centralized in Rome, not only regarding the Bible and religious doctrine, but also understandings of gender, sexuality and morality. Exciting and revolutionary, After Jesus Before Christianity provides fresh insights into the real history behind how the Jesus movement became Christianity